ربندر ناتھ ٹیگور کے ناول گورا کا مابعد نوآبادیاتی مطالعہ: Postcolonial Study of Rabindranath Tagore's Novel Gora (Research Journal Tahqeeqat, 2024)
This research article investigates the postcolonial aspects of Rabindranath Tagore’s novel Gora, a pivotal work addressing the socio-cultural and religious dynamics of colonial India. The novel delves into the transformative effects of British colonial rule, including the erosion of indigenous identities, cultural alienation, and the imposition of Western ideologies. It reflects the struggles of the colonized through the lens of mimicry, hybridity, ambivalence, and cultural differences, drawing on Homi K. Bhabha’s postcolonial theories.Key characters such as Gora, Anandamoyi, and Paresh Babu embody the conflicts between tradition and modernity, faith and scepticism, and resistance and acceptance of colonial ideologies. Gora’s identity crisis, Anandamoyi’s tolerance and defiance of rigid social norms, and Paresh Babu’s rationalism highlight the complex interplay of personal and cultural struggles in a colonized society. The narrative further critiques the divisions fostered by colonial policies, such as caste hierarchies and religious segregation, and their enduring impact on Indian society.Gora also portrays the duality of colonial mimicry—how adopting Western practices both empowers and alienates the colonized. The characters' dilemmas reflect broader societal tensions, underscoring the challenges of cultural negotiation and the loss of authentic identity.Ultimately, this paper reveals Gora as a profound critique of colonialism, advocating for social harmony, humanism, and the reclamation of indigenous cultural values. Tagore’s work remains a timeless exploration of the psychological and cultural ramifications of imperialism and the resilience of human spirit in the face of subjugation.